2013
DOI: 10.1186/1471-2407-13-368
|View full text |Cite|
|
Sign up to set email alerts
|

Axin gene methylation status correlates with radiosensitivity of lung cancer cells

Abstract: BackgroundWe previously reported that Axin1 (Axin) is down-regulated in many cases of lung cancer, and X-ray irradiation increased Axin expression and inhibited lung cancer cells. The mechanisms, however, were not clear.MethodsFour lung cancer cell lines were used to detect the methylation status of Axin with or without X-ray treatment. Real-time PCR was used to quantify the expression of Axin, and western blot analysis was applied to measure protein levels of Axin, β-catenin, Cyclin D1, MMP-7, DNMTS, MeCP2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…The AXIN2 gene may be the gene for dental agenesis that makes the connection to breast cancer. First, the AXIN2 gene has been mapped to chromosome 17q23-q24, which is a region that has a heterozygosity (LOH) in breast cancer [26]. Second, it was identified in high-grade breast tumors [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AXIN2 gene may be the gene for dental agenesis that makes the connection to breast cancer. First, the AXIN2 gene has been mapped to chromosome 17q23-q24, which is a region that has a heterozygosity (LOH) in breast cancer [26]. Second, it was identified in high-grade breast tumors [26].…”
Section: Discussionmentioning
confidence: 99%
“…First, the AXIN2 gene has been mapped to chromosome 17q23-q24, which is a region that has a heterozygosity (LOH) in breast cancer [26]. Second, it was identified in high-grade breast tumors [26]. Third, it was found that the SNPs in AXIN2 were breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…JUN and FOS also induce apoptotic cell death in cancer [ 20 ]. The MeCP2 protein is more highly expressed in most cancer tissues than in corresponding noncancerous tissues [ 21 ]. The up-regulation of apoptosis-related genes by MeCP2 RNA silencing suggests that the apoptosis-related genes might be suppressed in tumors with high MeCP2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of six genes ( WDR42A, HNRNPA0, HIS1, RBM12, CYP7B1 and FOXC1 ) were decreased to below 25% of the control levels. Three genes ( HNRPA0, HIS1 , and FOXC1 ) have anti-apoptotic and proliferative functions [ 21 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray-induced inhibition of lung cancer cells is mediated by enhanced expression of the Axin gene via genomic DNA demethylation and histone acetylation. Mechanically, it has been shown that MECP2 represses histone deacetylase, leading to transcriptional activation of the Axin gene via histone acetylation, thus suggesting a role for MECP2 in cancer prevention (Yang et al, 2013a, Esteller, 2005).…”
Section: Mecp2 and Human Diseasesmentioning
confidence: 99%